Hearing aid use and cognition in older adults: Can we delay decline or even improve cognitive function?: Epidemiology: Sensory impairment and cognition. (7th December 2020) - Sarant, Julia; Harris, David; Busby, Peter; Maruff, Paul T; Schembri, Adrian; Phillips, Jocelyn; Nixon, Grace; Lemke, Ulrike; Launer, Stefan; Tomlin, Dani; Dowell, Richard
Abstract: Background: Hearing loss is associated with accelerated cognitive decline in older adults, and has been identified as a modifiable risk factor for dementia. Although hearing aids are a successful treatment for hearing loss, it is unknown whether hearing aid use can delay the onset of cognitive decline or improve cognitive function in older adults with hearing loss. This prospective longitudinal study is investigating the effect of hearing aid use on cognitive decline and addresses many of the methodological limitations of previous studies. Method: Patients are recruited from the University of Melbourne Academic Hearing Aids Audiology Clinic and assessed before and every 18 months after hearing aid fitting. When numbers are sufficient, results will be compared with those of a control group of approximately 400 participants of a cohort study of ageing in older adults. Assessments include cognitive function (visually presented computerised assessment battery), hearing, speech perception, quality of life, activity, diet, loneliness and isolation, anxiety, depression, medical health and genetic risk. Result: At baseline, multiple linear regression for 98 participants (62‐82 years), controlling for age, gender, cardiovascular conditions, education, and working/retired, with mean better ear PTA 31dB showed hearing loss and age predicted significantly poorer executive function, while tertiary education predicted significantly better executive function and visual learning. At 18‐month follow up, results for a subset of participants showed significant improvements in speech perception, listening disability and quality of life. Group mean scores across the cognitive assessment battery showed no significant decline and executive function was significantly improved. There was either clinically significant improvement or stability for executive function for over 97% of the subset, and for females for working memory, visual learning and visual attention, despite significantly greater hearing loss over this period. Conclusion: Despite a small initial sample size, hearing loss, age and education significantly predicted baseline cognitive function. At 18‐month follow up, the majority of participants had either remained stable or demonstrated a meaningful clinical improvement in cognitive function, with significant group mean improvements for executive function and working memory. Treatment of hearing loss with hearing aids may delay cognitive decline. These are initial results, and further follow up is required.